2013
DOI: 10.1007/s00210-013-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Activated peroxisomal fatty acid metabolism improves cardiac recovery in ischemia-reperfusion

Abstract: Depressed oxidation of long chain fatty acids (LCFA) in heart ischemia leads to acute accumulation of LCFA metabolites that impair the functioning of the mitochondria. We hypothesized that reduced activity of carnitine palmitoyltransferase-I (CPT-I) might activate peroxisomal LCFA oxidation and protect mitochondrial function in ischemia and reperfusion. In the present study, despite the long-term threefold reduction in L-carnitine content by 3-(2,2,2-trimethylhydrazinium)-propionate, the uptake and oxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
3
40
2
3
Order By: Relevance
“…We then determined the effects of Methyl-GBB on the uptake and oxidation of LCFA in an isolated heart. In contrast to the previously observed effects of meldonium (Liepinsh et al, 2013b), the oxidation rate of labelled palmitate in the isolated heart was decreased by 40% ( Figure 4A). An increase in LCFA oxidation was observed after reperfusion in Methyl-GBB-treated group ( Figure 4A).…”
Section: Lcfas and Glucose Oxidationcontrasting
confidence: 99%
See 3 more Smart Citations
“…We then determined the effects of Methyl-GBB on the uptake and oxidation of LCFA in an isolated heart. In contrast to the previously observed effects of meldonium (Liepinsh et al, 2013b), the oxidation rate of labelled palmitate in the isolated heart was decreased by 40% ( Figure 4A). An increase in LCFA oxidation was observed after reperfusion in Methyl-GBB-treated group ( Figure 4A).…”
Section: Lcfas and Glucose Oxidationcontrasting
confidence: 99%
“…In previous studies, we have observed an increase in the nuclear content of PPAR‐α and PGC‐1α, as a response to decreased L‐carnitine content (Liepinsh et al ., 2011c; 2013b). The compensatory changes in the expression of the genes related to FAO and the redirection of LCFA flux from the mitochondria to the peroxisomes are clearly beneficial to preserve mitochondrial function and recovery after heart ischaemia (Liepinsh et al ., ). In this study, we observed that the decrease in L‐carnitine content did not induce substantial changes in gene expression involved in LCFA metabolism in normoxic hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case where peroxisome biogenesis is completely blocked, such treatment also results in other mitochondrial perturbations, including structural alterations of the inner mitochondrial membrane [57,58,59], a reduction in the activities of multiple respiratory chain complexes [57,58,59], reduced mitochondrial DNA abundance [57], and an increase in mitochondrial volume [57,59]. On the other hand, an increase in catalase activity [109,114], peroxisomal β-oxidation [115] or peroxisome number [116] has been reported to ameliorate mitochondrial fitness and protect these organelles against oxidative insults. In reverse, to the best of our knowledge, there are no published studies that have addressed how specific defects in mitochondrial functions affect the redox state of peroxisomes, and this issue remains an unresolved open question.…”
Section: Metabolic Interplaymentioning
confidence: 99%